Nα-1, 3-Benzenedicarbonyl-Bis-(Amino Acid) and Dipeptide Candidates: Synthesis, Cytotoxic, Antimicrobial and Molecular Docking Investigation - Naglah AM; Moustafa GO; Elhenawy AA; Mounier MM; El-Sayed H; Al-Omar MA; Almehizia AA; Bhat MA (Dove Medical Press, 2021)
Ahmed M Naglah,1,2 Gaber O Moustafa,2 Ahmed A Elhenawy,3,4 Marwa M Mounier,5 Heba El-Sayed,6 Mohamed A Al-Omar,1 Abdulrahman A Almehizia,1,7 Mashooq A Bhat7 1Department of Pharmaceutical Chemistry, Drug Exploration & Development Chair (DEDC), College of Pharmacy, King Saud University, Riyadh, 11451, Saudi Arabia; 2Peptide Chemistry Department, Chemical Industries Research Division, National Research Centre, Cairo, Egypt; 3Chemistry Department, Faculty of Science, Al-Azhar University (Boys’Branch), Cairo, Egypt; 4Chemistry Department, Faculty of Science, Albaha University, Al Baha, Saudi Arabia; 5Pharmacognosy Department, Pharmaceutical and Drug Industries Research Division, National Research Centre, Giza, Egypt; 6Botany and Microbiology Department, Faculty of Science, Helwan University, Helwan, Egypt; 7Department of Pharmaceutical Chemistry, College of Pharmacy, King Saud University, Riyadh, 11451, Saudi ArabiaCorrespondence: Gaber O Moustafa; Ahmed Elhenawy Tel +201003123355; +966599044526Email gosman79@gmail.com; elhenawy_sci@hotmail.comPurpose: The objective of our work was to prepare a potent and safe antimicrobial and anticancer agents, through synthesis of several peptides and examine their biological activities, namely as, cytotoxically potent and antimicrobial and antifungal agents.Introduction: Multidrug-resistant microbial strains have arisen against all antibiotics in clinical use. Infections caused by these bacteria threaten global public health and are associated with high mortality rates.Methods: The main backbone structure for the novel synthesized linear peptide is Nα-1, 3-benzenedicarbonyl-bis-(Amino acids)-X, ( 3– 11). A computational docking study against DNA gyrase was performed to formulate a mode of action of the small compounds as antimicrobial agents.Results: The peptide-bearing methionine-ester ( 4) exhibited potent antimicrobial activity compared to the other synthesized compounds, while, peptide ( 8), which had methionine-hydrazide fragment was the most potent as antifungal agent against Aspergillus niger with 100% inhibition percent. Compounds ( 6 and 7) showed the highest potency against breast human tumor cell line “MCF-7” with 95.1% and 79.8% of cell inhibition, respectively. The nine compounds possessed weak to moderate antiproliferative effect over colon tumor cell line. The docking results suggest good fitting through different hydrogen bond interactions with the protein residues. In silico ADMET study also evaluated and suggested that these compounds had promising oral bioavailability features.Conclusion: The tested compounds need further modification to have significant antimicrobial and antitumor efficacy compared to the reference drugs.Keywords: anticancer, antimicrobial activity, linear-peptides, Nα-1, 3-benzenedicarbonyl-bis-peptides, molecular docking